2016
DOI: 10.1021/acsphotonics.6b00700
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Confinement via Spin–Orbit Interaction in Anisotropic Dielectrics

Abstract: We investigate electromagnetic propagation in uniaxial dielectrics with a transversely varying orientation of the optic axis, the latter staying orthogonal everywhere in the propagation direction. In such a geometry, the field experiences no refractive index gradients, yet it acquires a transversely modulated Pancharatnam–Berry phase, that is, a geometric phase originating from a spin–orbit interaction. We show that the periodic evolution of the geometric phase versus propagation gives rise to a longitudinally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…This means that the polarization of the field will always vary while evolving along z, in turn leading to the occurrence of a transversely-varying PBP, whenever θ is not uniform. In accordance with the former statement, in the case of linear birefringence it is well known that the wavefront is strongly affected by the PBP, both for short [12,16,19] or long propagation [24,27] with respect to the Rayleigh distance. Light propagation changes drastically in the presence of circular birefringence, that is, 2D = ( 1 , −iγ; iγ, 2 ), where γ is the modulus of the gyration vector.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This means that the polarization of the field will always vary while evolving along z, in turn leading to the occurrence of a transversely-varying PBP, whenever θ is not uniform. In accordance with the former statement, in the case of linear birefringence it is well known that the wavefront is strongly affected by the PBP, both for short [12,16,19] or long propagation [24,27] with respect to the Rayleigh distance. Light propagation changes drastically in the presence of circular birefringence, that is, 2D = ( 1 , −iγ; iγ, 2 ), where γ is the modulus of the gyration vector.…”
supporting
confidence: 69%
“…[5,6,8] where geometric optics is used, here the wave behavior of the electromagnetic radiation is accounted for. Differently from the case of linear birefringence [24], we demonstrate that in optically active media the two circular polarizations see a photonic potential reversed in sign, yielding polarizationdependent guiding and SHE. Let us consider the monochromatic propagation of an electromagnetic field [amplitude ∝ exp (−iωt)] in an inhomogeneous anisotropic material.…”
contrasting
confidence: 67%
“…In a recent Letter we showed that light propagates under the influence of an effective photonic potential, leading to leaky guided modes for bell-shaped distributions of the optic axis rotation [35] (Fig. 1).…”
Section: Introductionmentioning
confidence: 93%
“…In Section III we generalize to the three-dimensional case the paraxial equations governing light propagation found in Ref. [35] to the case of long (with respect to the Rayleigh length) samples. We also Gaussian distribution of the rotation angle θ on the plane xy when maximum rotation is 90 • : the arrows correspond to the local optic axis (i.e., the extraordinary axis), superposed to the spatial distribution of θ represented as a color map.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation